Comparative Effects of Roux-en-Y Gastric Bypass and Sleeve Gastrectomy on Glucose Homeostasis and Incretin Hormones in Obese Type 2 Diabetic Patients: A One-Year Prospective Study - Nosso, G.; Griffo, E.; Cotugno, M.; Saldalamacchia, G.; Lupoli, R.; Pacini, G.; Riccardi, G.; Angrisani, L.; Capaldo, B. (Hormone and Metabolic Research, 2016)
The aim of the work was to compare the hormonal and the metabolic mechanisms involved in weight loss and remission of T2DM one year after Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) in morbidly obese type 2 diabetic (T2DM) patients. Insulin sensitivity, insulin secretion, and the gastrointestinal (GI) hormone response to a mixed meal test (MMT) were evaluated before and one year after BS (14 RYGB and 19 VSG). RYGB and VSG groups had similar characteristics at baseline. Weight loss at one year was similar in the 2 groups (ΔBMI%: − 32±10 and − 30±7%, p=0.546). Insulin sensitivity and insulin secretion improved similarly after either procedures with a similar rate in T2DM remission (86% in RYGB and 76% in VSG). Meal-stimulated GLP-1 levels increased after both procedures reaching significantly higher levels after RYGB (p=0.0001). GIP response to MMT decreased to a similar extent after the 2 interventions (p=0.977). Both fasting and post-meal ghrelin concentrations were markedly suppressed after VSG and significantly lower than RYGB (p=0.013 to p=0.035). The improvement of insulin sensitivity and beta-cell function was significantly associated with weight loss (p=0.014 to p=0.035), while no relation was found with the changes in GI hormones. In conclusion, in morbidly obese T2DM patients, RYGB and VSG result in similar improvements of the glucose status in the face of different GI hormonal pattern. Weight loss is the key determinant of diabetes remission one year after surgery.
Keywords: bariatric surgery; diabetes; GI hormones; insulin sensitivity; insulin secretion